Attitude and awareness towards periodontal health among health care and non-health care professionals - Surekha Rathod; Farooque Khan; Trupti Sarda (SRM Journal of Research in Dental Sciences, 2016)
Background and Aim: The behavior of oral health care providers and their attitudes toward their own health refl ect their understanding of the importance of preventive dental procedure and improving the oral health of patients. The attitude toward oral health determines the health status of the oral cavity. A cross-sectional study conducted among the health care professionals and non-health care professionals to assess attitude and awareness towards periodontal health. Materials and Methods: The data pertaining to their knowledge, attitude, and practice about oral health was gathered using a self-administered questionnaire containing 13 questions which were a multiple options questionnaire. The questionnaire was distributed among 798 subjects within the age range of 17-25 years (402 were distributed among health care professionals and among 398 non-health care professionals). Results: Health care professionals visited their dentist regularly, had less dental problems, used proper tooth-brushing technique and other interdental aids, had a good lifestyle as compared to non-health care professionals. Conclusion: So the basic knowledge about dentistry should be incorporated in the syllabus.